Can photoemission tomography be useful for small, strongly-interacting adsorbate systems?. (4th April 2019) - Egger, Larissa; Kollmann, Bernd; Hurdax, Philipp; Lüftner, Daniel; Yang, Xiaosheng; Weiss, Simon; Gottwald, Alexander; Richter, Mathias; Koller, Georg; Soubatch, Serguei; Tautz, F Stefan; Puschnig, Peter; et al.
Abstract: Molecular orbital tomography, also termed photoemission tomography, which considers the final state as a simple plane wave, has been very successful in describing the photoemisson distribution of large adsorbates on noble metal surfaces. Here, following a suggestion by Bradshaw and Woodruff (2015 New J. Phys. 17 013033), we consider a small and strongly-interacting system, benzene adsorbed on palladium (110), to consider the extent of the problems that can arise with the final state simplification. Our angle-resolved photoemission experiments, supported by density functional theory calculations, substantiate and refine the previously determined adsorption geometry and reveal an energetic splitting of the frontier π -orbital due to a symmetry breaking which has remained unnoticed before. We find that, despite the small size of benzene and the comparably strong interaction with palladium, the overall appearance of the photoemission angular distributions can basically be understood within a plane wave final state approximation and yields a deeper understanding of the electronic structure of the interface. There are, however, noticeable deviations between measured and simulated angular patterns which we ascribe to molecule-substrate interactions and effects beyond a plane-wave final state description.